Exercise training decreases mitogen-activated protein kinase phosphatase-3 expression and suppresses hepatic gluconeogenesis in obese mice - Souza Pauli, Luciana Santos; Chiarreotto Ropelle, Eloize Cristina; Souza, Claudio Teodoro de; Cintra, Dennys Esper; Ramos da Silva, Adelino Sanchez; Rodrigues, Barbara de Almeida; Moura, Leandro Pereira de [UNESP]; Marinho, Rodolfo [UNESP]; Oliveira, Vanessa de; Katashima, Carlos Kiyoshi; Pauli, Jose Rodrigo; Ropelle, Eduardo Rochete (Wiley-Blackwell, 2014)
Key points summaryWhen the hepatic insulin signaling is compromised, there is an inadequate suppression of gluconeogenic pathways, leading the organism to high levels of glucose.Studies with animals with obesity induced by high fat diet or genetically modified showed increased MKP-3 expression and MKP-3/Foxo1 association in liver, with a consequent increase in blood glucose concentration, development of insulin resistance and DM2.As a non-pharmacological strategy recognized and indicated for prevention and treatment of diabetes is the regular practice of physical exercise.In this study we demostrated that physical training is an important tool capable of reducing insulin resistance in the liver by reducing the inflammatory process, including the inhibition of MKP-3 and, therefore, suppress gluconeogenic program in obesity rats.The understanding of these new mechanisms by which physical training regulates glucose homeostasis has critical importance to health professionals for the understanding and prevention of diabetes.Insulin plays an important role in the control of hepatic glucose production. Insulin resistant states are commonly associated with excessive hepatic glucose production, which contributes to both fasting hyperglycaemia and exaggerated postprandial hyperglycaemia. In this regard, increased activity of phosphatases may contribute to the dysregulation of gluconeogenesis. Mitogen-activated protein kinase phosphatase-3 (MKP-3) is a key protein involved in the control of gluconeogenesis. MKP-3-mediated dephosphorylation activates FoxO1 (a member of the forkhead family of transcription factors) and subsequently promotes its nuclear translocation and binding to the promoters of gluconeogenic genes such as phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase (G6Pase). In this study, we investigated the effects of exercise training on the expression of MKP-3 and its interaction with FoxO1 in the livers of obese animals. We found that exercised obese mice had a lower expression of MKP-3 and FoxO1/MKP-3 association in the liver. Further, the exercise training decreased FoxO1 phosphorylation and protein levels of Peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1 alpha) and gluconeogenic enzymes (PEPCK and G6Pase). These molecular results were accompanied by physiological changes, including increased insulin sensitivity and reduced hyperglycaemia, which were not caused by reductions in total body mass. Similar results were also observed with oligonucleotide antisense (ASO) treatment. However, our results showed that only exercise training could reduce an obesity-induced increase in HNF-4 alpha protein levels while ASO treatment alone had no effect. These findings could explain, at least in part, why additive effects of exercise training treatment and ASO treatment were not observed. Finally, the suppressive effects of exercise training on MKP-3 protein levels appear to be related, at least in part, to the reduced phosphorylation of Extracellular signal-regulated kinases (ERK) in the livers of obese mice.